CHLOROQUINE AND HYDROXYCHLOROQUINE IN THE MANAGEMENT OF COVID-19: A SYSTEMATIC REVIEW - Zapata, Jonathan Melena (2022)
Due to the new coronavirus (SARS-CoV-2) pandemic, health authorities of some of the most affected countries implemented the emerging use of chloroquine and hydroxychloroquine for the management of COVID-19 (associated disease). Nevertheless, the clinical benefits of such drugs have not yet been fully elucidated. To assess the safety, efficacy, and prophylactic use of chloroquine and its derivatives in the clinical management of COVID-19, a literature search of the databases was conducted through Pubmed, The Cochrane Library, Embase, and Lilacs from November 2019 until June 7th, 2020. The reviewers independently and in duplicate selected studies for inclusion and assessment of risk of bias. Thirteen studies were included: seven cohorts, five randomized clinical trials and one non-randomized clinical trial. Four studies reported clinical benefits of using chloroquine or hydroxychloroquine alone or in combination with macrolides for the treatment of COVID-19, eight studies reported an increased risk of life-threatening adverse effects due to the use of either drug, and one study did not report any benefit for prophylaxis. The urgent need for studies evaluating the safety and clinical efficacy of chloroquine and its derivatives in the management of COVID-19 is highlighted.